2022
DOI: 10.46690/ager.2023.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of response behaviors of natural gas hydrate reservoir around wellbore induced by water jet slotting

Abstract: The trial production of natural gas hydrate reservoirs remains poor. Reasonable reservoir reconstruction, which can improve formation permeability, is an important approach to increasing the efficiency and enhancing production. In this work, water jet slotting is proposed to reconstruct an natural gas hydrate reservoir near a wellbore. The spatial slots formed by water jet slotting not only directly constitute high-permeability channels, but also generate disturbances to the surrounding in-situ sediment. Water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Li et al 40 analyzed the mechanism of wax clogging in the process of moving the pipe cleaner in front of the wax plug and in the process of not cleaning. Huang et al 41 found that radial water jet slotted grouting can effectively improve the gas recovery rate of horizontal wells. Pang et al 42 prepared a high temperature resistant viscosity-reducing agent suitable for water-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 40 analyzed the mechanism of wax clogging in the process of moving the pipe cleaner in front of the wax plug and in the process of not cleaning. Huang et al 41 found that radial water jet slotted grouting can effectively improve the gas recovery rate of horizontal wells. Pang et al 42 prepared a high temperature resistant viscosity-reducing agent suitable for water-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%